2011
DOI: 10.3892/ol.2011.297
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of secreted protein, acidic and rich in cysteine in human laryngeal and hypopharyngeal carcinoma

Abstract: Abstract. Secreted protein, acidic and rich in cysteine (SPARC) has been found to be involved in various stages of tumor progression such as migration, invasion, extracellular matrix deposition and angiogenesis. To obtain an insight into the role of SPARC in the progression of laryngeal and hypopharyngeal carcinoma, we investigated SPARC transcription levels and promoter methylation in carcinoma cell lines and primary tumors. Reverse transcription-PCR showed that SPARC was silenced in laryngeal and hypopharyng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, other studies suggested that SPARC induced endoplasmic reticulum stress leading to autophagy-mediated apoptosis in neuroblastoma (12), and RNA interference against SPARC promoted the growth of malignant glioma cells (13). The aberrant methylation of SPARC was identified in human laryngeal and hypopharyngeal carcinomas (71). In addition, SPARC was observed to be involved in the transformation of hamster oral mucosa from precancerous lesions to squamous cell carcinoma (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies suggested that SPARC induced endoplasmic reticulum stress leading to autophagy-mediated apoptosis in neuroblastoma (12), and RNA interference against SPARC promoted the growth of malignant glioma cells (13). The aberrant methylation of SPARC was identified in human laryngeal and hypopharyngeal carcinomas (71). In addition, SPARC was observed to be involved in the transformation of hamster oral mucosa from precancerous lesions to squamous cell carcinoma (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…The same role for the molecule was demonstrated in ESCC, in which high SPARC expression closely associates with ESCC metastasis [ 132 ]. Overall, the level of SPARC in the UADT SCC TME represents a potential predictor of poor prognosis and has been shown also to associate with impaired sensitivity to chemotherapy [ 133 ]. All these evidence prompted to propose SPARC as a therapeutic target for these types of tumors [ 134 ].…”
Section: Ecm In Uadt Scc: An Intertwined Storymentioning
confidence: 99%
“…It is silenced through promoter methylation in metastatic and aggressive prostate cancer cells, with its promoter hypermethylation inversely correlating with prostate cancer patients’ disease-free survival [85]. Hypermthylation-induced silencing of SPARC has also been reported in pancreatic cancer [86], ovarian cancer [87] hepatocellular carcinoma [88] and laryngeal and hypopharyngeal carcinomas [89]. Low TIMP3 expression in many cancers, including prostate cancer, has been demonstrated to facilitate metastatic potential of tumor cells, due to an increase in the activity of matrix metalloproteinase activity in the tumor microenvironment [90].…”
Section: Epigenetics In Cancer Health Disparitiesmentioning
confidence: 99%